2013
DOI: 10.1530/rep-12-0220
|View full text |Cite
|
Sign up to set email alerts
|

The expression of fibroblast growth factor receptors during early bovine conceptus development and pharmacological analysis of their actions on trophoblast growth in vitro

Abstract: The overall aim of this work was to examine the expression profiles for fibroblast growth factor receptors (FGFRs) and describe their biological importance during bovine pre-and peri-implantation conceptus development. FGFR1 and FGFR2 mRNAs were detected at 1-, 2-, 8-cell, morula and blastocyst stages whereas FGFR3 and FGFR4 mRNAs were detected after the 8-cell stage but not earlier.The abundance of FGFR1, FGFR3, and FGFR4 mRNAs increased at the morula and blastocyst stages. Immunofluorescence microscopy detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 63 publications
0
21
0
2
Order By: Relevance
“…Ozawa et al (2013) demonstrated the presence of FGFR1, FGFR2, FGFR3 and FGFR4 in bovine embryos up to the blastocyst stage and showed that FGFR activation is needed to maximise IFNT expression and permit outgrowth formation. However, there is a paucity of data relating to posthatching stages of development, probably a reflection of the difficulty in obtaining such stages in vivo.…”
Section: Introductionmentioning
confidence: 96%
“…Ozawa et al (2013) demonstrated the presence of FGFR1, FGFR2, FGFR3 and FGFR4 in bovine embryos up to the blastocyst stage and showed that FGFR activation is needed to maximise IFNT expression and permit outgrowth formation. However, there is a paucity of data relating to posthatching stages of development, probably a reflection of the difficulty in obtaining such stages in vivo.…”
Section: Introductionmentioning
confidence: 96%
“…FGF1, FGF2 and FGF4 have been reported to be expressed in preimplantation embryos. 20,31,32 Here, we found that the formation of expanded blastocysts was arrested only after the knockdown of FGF2 in TEs in vitro, which suggests that FGF2 is required in TEs for the development of expanded blastocysts. The knockdown of FGF2 in TEs affected the growth of expanded blastocysts, which could be reversed when the embryos were cultured with 1000 ng/ml exogenous FGF2 for 12 h. However, this rescue was completely abolished when the activation of FGF2 was eliminated by the application of an FGF2 antibody.…”
Section: Discussionmentioning
confidence: 65%
“…18,20,[31][32][33][34][35] However, the functions of these molecules in TEs that lead to the formation of the blastocyst as well as the underlying mechanism have not been elucidated. The present study has demonstrated for the first time that endogenous FGF2 secreted by TEs can regulate protein expression and distribution in TEs via the FGFR2-mediated activation of PKC and p38, which are important for the development of expanded blastocysts (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone H2A (H2A) was used as the reference transcript for examining changes in transcript abundance from one-cell to blastocyst stages. Previous work verified the consistency of expression for H2A between the one-cell and blastocyst stages in bovine embryos (Robert et al 2002;Ozawa et al 2013). Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) was used as the reference transcript for blastocyst studies given its consistency of expression after blastocyst formation (Purcell et al 2009).…”
Section: Methodsmentioning
confidence: 92%